Система коефіцієнтів рентабельності активів: сучасні тенденції розрахунку й аналізу (на прикладі підприємств сфери гостинності) - Чайка, Тетяна Юріївна; Мартинова, Вікторія Вікторівна; Невміріч, Дмитро Віталійович (Національний авіаційний університет, 2019)
У статті проаналізовано наявні методики розрахунку показників рентабельності активів, виявлено наявні неузгодженості в підходах до розрахунку однойменних показників. Емпіричний економіко-статистичний аналіз проводився за даними відкритої фінансової звітності українських підприємств сфери гостинності. Досліджено аналітичні можливості коефіцієнтів рентабельності активів, які сконструйовані на основі чистого прибутку, прибутку до вирахування відсотків та податків (EBIT), а також прибутку до вирахування відсотків, податків та амортизації основних засобів і нематеріальних активів (EBITDA). Розроблено практичні рекомендації щодо вибору конкретної форми метрики рентабельності активів залежно від цілей аналізу та необхідності врахування структури капіталу, величини фінансового левериджу, облікової політики, галузевої специфіки забезпеченості основними засобами, методів нарахування амортизаційних відрахувань та життєвого циклу підприємства.

The current differences in methodological approaches of calculating return on assets ratios are a significant obstacle to the success of comparative analytics. Often, indicators that have the same name are calculated in a completely different way. Features forming national financial statements have an impact on the choice of methods for calculating the respective ratios and thus lead to errors when comparing the profitability of assets of business entities of different nationalities. In this regard, it is necessary to clarify the system of indicators of return on assets and improve the methodological approaches to their calculation based on open financial statements. It is necessary to develop a unified approach to the calculation of return on assets ratios, only in this case it is possible to conduct high-quality and relevant comparative analytical work in this area. In this article, an analysis of existing methods of calculating indicators of profitability of assets has been carried out, and there is revealed discrepancies in approaches to calculating indicators of the same name. Analyzed the analytical capabilities of asset profitability ratios, designed on the basis of Net Profit, Earnings before Interest and Taxes (EBIT) and Earnings before Interest, Taxes, Depreciation and Amortization (EBITDA). Practical recommendations have been developed for choosing a specific form of the asset profitability metric depending on the goals of the analysis and the need to take into account the capital structure, the amount of financial leverage, accounting policies, industry-specific security of fixed assets, methods for calculating depreciation charges and the life cycle of an enterprise. The possibilities of forming a set of profitability indicators of assets with their specification for individual groups of assets in accordance with various classification criteria and taking into account the specific objectives of the analysis are considered. Empirical economic and statistical analysis was carried out according to open financial statements of Ukrainian hospitality enterprises.
The system of asset profitability ratios: current trends in calculation and analysis (on the example of hospitality industry enterprises)
Keywords: рентабельність активів (ROA); фінансова звітність; чистий прибуток (NP); рентабельність необоротних активів (ROFA); рентабельність оборотних активів (RCA); класифікація активів; return on assets (ROA); financial statements; net profit (NP); return on fixed assets (ROFA); return on current assets (RCA); asset classification